PENGOLAHAN LIMBAH JERUK SIAM MENJADI OLAHAN JELLY SPIRAL SEBAGAI PANGAN KREATIF DI KECAMATAN TEBAS KABUPATEN SAMBAS: Siamese Orange Waste Treatment Into Processed Jelly Spirals As Creative Food In Tebas District Sambas Regency - Renol Burjulius; Sonty Lena; Kiki Kristiandi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Siamese oranges in Sambas Regency have the potential to be processed into food products that provide regional characteristics. The area of this plant land is evenly spread over 19 sub-districts in Sambas Regency. However, the total area of plantations owned by Tebas District with a range of area is 1,240,235 per year 2015-2020. The potential of the land area owned by Sambas Regency can have an impact on productivity by-products, so that efforts are made to reduce the incidence of fruit that does not match market demand, processing Siamese orange waste into Jelly Spirals is carried out. Participants who joined in this process were 30 participants and divided into 5 teams with each team consisting of 6 people and divided. The approach used in this activity uses the participatory action research (PAR) method. Participants are people who focus on citrus agricultural products. The results of this activity received a positive response from the community because it provided new information on processed Siamese oranges as raw materials and provided new experiences from this processing activity.